Komunikasi Interpersonal Pasangan Suami Istri Beda Agama dalam Mewujudkan Keharmonisan Rumah Tangga (Studi Kasus Kampung Madras Medan) - Nabillah Nabillah; Sori Monang; Abdul Karim Batubara (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study looks at how married couples from various religious backgrounds communicate with one another. This has evolved into a phenomenon that is ingrained in people's daily lives. All married couples, especially those who come from diverse religious backgrounds, want their homes to be clean and harmonious. Religious differences have been a source of troubles and disagreements in marriage. The S-O-R Theory is used in this study. This study used a qualitative descriptive research method, which included in-depth interviews and observations of the married couples under study. According to the findings of the study, married couples from various religious backgrounds can communicate their differences through interpersonal communication. The achievement of successful interpersonal communication is characterized by openness, empathy, support, a sense of positivity, and equality in the dialogue that occurs. There is a sense of appreciation for diversity, as well as a mature attitude about adjusting to large families with diverse beliefs.